Effectiveness of augmentative alternative communication therapy in children with cerebral palsy with expressive speech delay - Prasanna, Priyanka; Gowda, Vykuntaraju K.; Shivappa, Sanjay K.; Hegde, Sandeep (International Journal of Contemporary Pediatrics, 2025)
Background: The objectives of the study were to determine the effectiveness of augmentative alternative communication therapy (AAC) in children with cerebral palsy (CP) and to correlate the outcome of AAC therapy with the communication function classification system (CFCS) and gross motor function system classification (GMFCS) levels. Methods: This is a prospective interventional study. Among the children satisfying the inclusion criteria, CFCS and GMFCS scoring, and the family impact of assistive technology scale AAC scoring (FIATS AAC) were taken. AAC therapy was administered based on the patient’s baseline communication skills, utilizing both aided and unaided techniques on a weekly follow-up basis. The outcome was assessed at 6 months following therapy by both the investigator and the speech therapist using the FIATS-AAC questionnaire. Results: All cohorts (n=101) had a predominant expressive language delay. Among 101 cohorts, 43.5% belonged to level 3 GMFCS, and 42.5% belonged to level 3 CFCS classification. 93.06% (n=94) used low-tech AAC, and 6.94% (n=7) used high-tech AAC. The correlation between baseline and follow-up FIATS AAC scores showed a significant improvement in the score, with a p<0.01. Conclusion: Children with expressive speech delay could benefit from AAC as it aids in communication with family and social interaction. Additionally, this study correlates the association between GMFCS and CFCS with AAC therapy.